(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The image of Herman Melville’s Moby Dick, foundational novel of the American narrative, is originated in the southern chilean sea. The repertory that precedes the literary work proposed by Wolfgang Iser presents a process in which different versions of the myth are written. The graphic novel Mocha Dick by Francisco Ortega (texts) and Gonzalo Martínez (artwork) is one of these versions of the myth. The chilean comic dialogues with the previous texts and proposes a review of Melville´s and the origins of the legendary white whale.